S72 Prediction of survival in pulmonary arterial hypertension using survival equations. Results from the pulmonary hypertension registry of the UK and Ireland. (2nd December 2011) - Ling, Y; Johnson, M K; Kiely, D; Condliffe, R; Elliot, C; Gibbs, S; Howard, L; Pepke-Zaba, J; Sheares, K; Corris, P; Fisher, A; Lordan, J; et al.
Abstract : Introduction: The NIH survival equation1 was developed in the 1980s and used in many clinical trials to show survival benefit. Since then, significant advances had been made in the diagnosis and management of pulmonary arterial hypertension (PAH). Several new equations have been developed to better predict survival in PAH. All these survival equations were derived using prognostic factors identified from a mixed incident and prevalent PAH cohort. However, prevalent patients have better survival compared to incident patients. Objectives: To determine applicability of currently available survival equations in incident idiopathic (IPAH), heritable and anorexigen-associated PAH. Methods: Retrospective observational study of all incident cases of IPAH, heritable and anorexigen-associated PAH diagnosed in the UK and Ireland between 1st January 2001 and 31st December 2009. Observed survival in the UK and Ireland was estimated using life table analysis and compared with predicted survival in the same patients calculated using the NIH, 1 French, 2 Pulmonary Hypertension Connection (PHC)3 and REVEAL4 Registry equations. Results: Total of 646 patients were diagnosed over the study period. Observed vs predicted survival were compared [Abstract S72 figure 1 ]. Conclusion: Survival equations derived from other mixed incident and prevalent pulmonary hypertension populations may not accurately predict survival of incident pulmonary arterial hypertension from the UK and Ireland. Differences in baseline characteristics, treatment practice and time period between our patients and survival equations derivation populations need to be taken into account when applying these equations in daily clinical practice.